Sistem Pengamanan Pintu Rumah Otomatis via SMS Berbasis Mikrokontroller ATMega328P - Muhammad Ridwan Asad; Oky Dwi Nurhayati; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
In this article, an automatic door security was designed used SMS, which serves as security for a microcontroller based door. This system was designed to facilitate the home user to lock the door and notice the condition of the house when the doors were left empty. The medium used is a phone by using SMS facility. This device consists of a sensor that is a “push button” that serves as input to inform the condition of the door to the microcontroller, microcontroller used is ATmega328P. Then Wavecom GSM Modem M1306B which serves as the sender and recipient SMS, using a solenoid to lock the door, and use the buzzer for alarm. The security system has been built with the working principles if there are people who want to try to enter and then numbers uninitialized on the microcontroller, the system will give a warning SMS notification to the user that